RESULTS OF PERCUTANEOUS NEPHROLITHOTOMY VIA MICRO-TUNNEL (14 Fr), WITHOUT URETERAL CATHETER PLACEMENT, ULTRASOUND GUIDED PANUCLEAR PATHOLOGY CONVENIENT USE of HOLMIUM LASER ADJUSTED SAINT PAUL GENERAL HOSPITAL FROM 2023-2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes and safety of 14 Fr super-mini percutaneous nephrolithotomy performed without ureteral catheter placement, using ultrasound-guided access and Holmium laser lithotripsy at Saint Paul General Hospital.Subjects and methods: A retrospective descriptive study was conducted on 120 patients who underwent 14 Fr super-mini percutaneous nephrolithotomy in the prone position from December 2023 to December 2025. The technique included no ureteral catheter placement, ultrasound-guided renal puncture, 14 Fr tract dilation, Holmium laser lithotripsy, no nephrostomy tube placement, and JJ sonde placement in all patients.Results: The mean age was 48.9 ± 21.8 years (11-79 years old), with males accounting for 65%. The mean stone size was 24.7 ± 8.3 mm; the most common stone locations were the lower calyx (39.2%) and renal pelvis (32.5%). Renal access was achieved through the middle calyx in 47.5%, the lower calyx in 44.2%, and the upper calyx in 8.3%. The mean lithotripsy and stone extraction time was 32.8 ± 23.2 minutes. Intraoperative bleeding occurred in 1.7% and postoperative bleeding in 0.8% of patients, with no cases requiring blood transfusion or angioembolization. Postoperative fever was observed in 6.7% of cases; no sepsis or organ injury was recorded. The mean VAS score was 2.5 ± 1.1. Hemoglobin levels decreased from 139.6 ± 31.8 to 128.9 ± 27.2, while creatinine levels were 80.3 ± 41.8 preoperatively and 85.1 ± 35.7 postoperatively. The early stone-free rate was 95.0%, increasing to 97.7% at one-month follow-up. No patient required additional intervention. The mean hospital stay was 2.9 ± 1.7 days.Conclusion: Ultrasound-guided 14 Fr super-mini percutaneous nephrolithotomy using Holmium laser at Saint Paul General Hospital achieved high stone-free rates, low complication rates, and short hospital stay, representing an effective and safe option for the management of renal stones measuring approximately 2-3 cm in clinical practice.
Keywords: Super mini-percutaneous nephrolithotomy, Holmium laser, renal stones.